La terra e la morte. The symbolic realism in the last poetry of Xabier Lete - Gurrutxaga Muxika, Alex (EGAN, 2021)
The aim of this article is to study the poetry of the last period of Xabier Lete, with a particular focus on symbolic realism. Taking into account the influence that the Italian writer Cesare Pavese had on Lete, we will analyze some of the most important spaces and times that appear symbolized in his last poetry. By investigating the meaning of these elements, we will be able to delve deeper into Lete’s poetry, highlighting the importance and value that symbolic realism has in his poetic thinking.